Wired/Wireless Internet Communications 15th IFIP WG 6.2 International Conference, WWIC 2017, St. Petersburg, Russia, June 21-23, 2017, Proceedings - Koucheryavy, Yevgeni; Mamatas, Lefteris; Matta, Ibrahim; Ometov, Aleksandr; Papadimitriou, Panagiotis; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book constitutes the proceedings of the 15th IFIP International Conference on Wired/Wireless Internet Communications, WWIC 2017, held in St. Petersburg, Russia, in June 2017. The 27 papers presented in this volume were carefully reviewed and selected from 76 submissions. They were organized in topical sections named: network analysis and dimensioning; 5G communications; network design and planning; network protocols; information technology; and circuit design. .
Network analysis and dimensioning -- Bargaining over Fair Channel Sharing between Wi-Fi and LTE-U Networks -- Time-Dependent SIR Analysis in Shopping Malls Using Fractal-Based Mobility Models.-Analysis and performance evaluation of SDN queue model -- Analysis of a retrial queue with limited processor sharing operating in the random environment -- Stationary Distribution of Waiting Time in MAP/G/1/N Queueing System with LIFO Service Discipline -- 5G communications. -Distributed Sleep Mode Power Control in 5G Ultra Dense Networks -- System Model for Multi-level Cloud Based Tactile Internet System. -Task Scheduling Scheme Based on Cost Optimization in 5G/Hetnets C-RAN -- Energy Efficiency Performance for 5G Cellular Networks -- Network design and planning -- Interaction of the IoT traffic generated by a Smart city segment with SDN core network -- Evaluation of Geocast Routing Trees on Random and Actual Networks -- A NURBS Based Technique for an Optimized Transmit Opportunity Map Processing in WLAN Networks -- Network protocols -- Load-Balancing Adaptive Clustering Refinement Algorithm for Wireless Sensor Network Clusters -- Simulation and Testing of a Platooning Management Protocol Implementation -- Research of Interaction between Applications of Augmented Reality and Control Methods of UAVs -- Energy-efficient Power Control and Clustering in Underlay Device to Multi-Device Communications -- Adaptive-Segmentation and Flexible-Delay Based Broadcasting Protocol For VANETs.-Information technology. -NetFlow Anomaly Detection Though Parallel Cluster Density Analysis in Continuous Time-Series -- Investigation of traffic pattern for the augmented reality applications -- Benefits of Multiply-cascaded TCP Tunnel with Network Coding over Lossy Networks -- Circuit design -- A Broadband Power Amplifier Applied in GSM/TD-SCDMA/WLAN System -- An 8-bit 6GS/s Current Steering DAC with Optimized Current Switch Drive -- IBIS-AMI based PAM4 Signaling and FEC Technique for 25 Gb/s Serial Link -- Spur-free MASH DDSM with Eliminable Dither -- A 20 Gb/s Wireline Receiver with Adaptive CTLE and Half-rate DFE in 0.13 m Technology.
Keywords: 9; Application software; Electronic digital computers -- Evaluation; Computer Communication Networks; Computer and Information Systems Applications; System Performance and Evaluation